(3eaJGM GdXaQ def QGe Ydhe cJGH Gddg HPgf MVQs - (3eMeO Hf CMeO GdYhaj,J (B1050 (3g` s
(3ChdgG (B:s
(3hHYO jbhd eMeO Hf CMeO GdYhaj gPG oeNJUQ ajeG Hjf MaU Ydi YGUe hHjf s
(3BNQgG (B:s
(3hbO PcQJ gPG GdHGH eaUdkG aj ZjQ gPG GdoeNJUQ hGddg GdgGOj ddUhGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B9 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B306s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs